Morphometric Approach to Quantitative Assessment of Thickness of Sediments Meandering Paleochannels of the Tyumen Formation of the West Siberian Oil and Gas Basin - T. V. Olneva; M. Yu. Oreshkova; A. V. Butorin; A. S. Egorov (Georesursy, 2024)
The article is devoted to implementation of morphometric analysis in process of qualitative and quantitative dynamic interpretation of seismic data. Essence of new approach is to predict reservoir capacity of channel genesis based on established dependencies between parameters “width of channel formation belt” and “thickness of channel deposits”. Interpretation of meandering river system demonstrates on example of one productive interval identified in the Tyumen formation. This article presents three variants of dependencies, two of which are the author’s and published for the first time. Authors have developed a program code in Python to automate morphometric analysis. Ranges of values predicted on basis of dependencies are correlated with results of quantitative dynamic analysis performed by inversion transformations, as well as with general ideas about sediment thickness of both modern river systems and paleosystems in geological formations of different ages.